2014
DOI: 10.1016/j.molcel.2014.08.014
|View full text |Cite
|
Sign up to set email alerts
|

A Genome-wide RNAi Screen Identifies Opposing Functions of Snai1 and Snai2 on the Nanog Dependency in Reprogramming

Abstract: SUMMARY Nanog facilitates ESC self-renewal and iPSC generation during the final stage of reprogramming. From a genome-wide siRNA screen using a Nanog-GFP reporter line we discovered opposing effects of Snai1 and Snai2 depletion on Nanog promoter activity. We further discovered mutually repressive expression profiles and opposing functions of Snai1 and Snai2 during the Nanog-driven final stage of reprogramming. We found that Snai1, but not Snai2, is both a transcriptional target and protein partner of Nanog in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
61
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 57 publications
6
61
0
Order By: Relevance
“…These findings (and the fact that reprogramming can be induced by smallmolecule inhibitors) suggest a complex interplay between cell fates . In accordance with these data, Gingold et al (2014) have found that during the Nanogdependent phases of reprogramming Snail 2 is active and antagonizes Snail 1; in subsequent phases, Snail1 acts as an effector (and partner) of Nanog, resulting in down-regulation miR290, thus allowing reprogramming.…”
Section: Emt and Cellular Reprogramingsupporting
confidence: 74%
“…These findings (and the fact that reprogramming can be induced by smallmolecule inhibitors) suggest a complex interplay between cell fates . In accordance with these data, Gingold et al (2014) have found that during the Nanogdependent phases of reprogramming Snail 2 is active and antagonizes Snail 1; in subsequent phases, Snail1 acts as an effector (and partner) of Nanog, resulting in down-regulation miR290, thus allowing reprogramming.…”
Section: Emt and Cellular Reprogramingsupporting
confidence: 74%
“…As mentioned before, except for a limited number of circumstances, Snail proteins mainly function as transcriptional repressors[14, 15]. As such, our data leaves us with 2 basic hypotheses as to how this may be occurring in T Conv and T Reg cells.…”
Section: Discussionmentioning
confidence: 53%
“…Once bound to target genes, Snail family members augment transcription through the recruitment of various chromatin modifiers via the SNAG domain[12, 13]. Although classically known as transcriptional repressors, a growing body of data supports the ability of Snail proteins to positively regulate their targets upon interaction with other transcription factors[14, 15]. …”
Section: Introductionmentioning
confidence: 99%
“…Snai1 and/or Snai2 have been shown to regulate expression of Nanog, the key pluripotency gene and regulator of embryonic stem cell self-renewal, both in embryonic stem cells [Gingold et al, 2014] and in mouse embryonic fibroblasts [Bermejo-Rodriquez et al, 2006]. Interestingly, during Nanog-driven induced pluripotent stem cell generation, Snai1 and Snai2 were found to have opposing roles -with Snai2 inhibiting cellular reprogramming and Snai1 enhancing it [Gingold et al, 2014].…”
mentioning
confidence: 99%
“…Interestingly, during Nanog-driven induced pluripotent stem cell generation, Snai1 and Snai2 were found to have opposing roles -with Snai2 inhibiting cellular reprogramming and Snai1 enhancing it [Gingold et al, 2014]. In the context of breast cancer cell lines, however, both SNAI1 and SNAI2 have been shown to induce a more stem cell-like phenotype characterised by increased selfrenewal [Mani et al, 2008].…”
mentioning
confidence: 99%